Pengaruh Kebijakan Pemerintah Daerah tentang Kearifan Lokal Penggunaan Noken Bagi ASN terhadap Produktivitas dan Penghasilan Mama Papua Pengrajin Noken di Distrik Mimika Baru, Kabupaten Mimika - Hasan Basri Umar; Andreas Alua (Universitas Cenderawasih, 2025)
This study aims to analyze the influence of local government policy regarding the cultural wisdom of noken usage by civil servants (ASN) on the productivity and income of mama-mama Papua—women artisans who craft noken—in Mimika Baru District, Mimika Regency. The background of this study stems from the dual effort to preserve local cultural heritage and to empower the economic capacity of communities, especially Papuan women, through the traditional craft of noken, which has been recognized by UNESCO as an intangible cultural heritage of humanity. This research employed a quantitative method with a survey approach, involving 35 respondents selected through accidental sampling from an estimated total population of 350 artisans. Data were collected through questionnaires, interviews, and observations, and analyzed using Path Analysis with the support of SPSS software. The findings indicate that the policy of noken use among ASN has a positive and significant effect on both the productivity and income of artisans. The path coefficient was 0.3524 for productivity and 0.2846 for income, with p-values of 0.0379 and 0.0442 respectively, at a 95% confidence level. These results show that the policy’s implementation effectively increases demand for noken products, which in turn encourages greater production, improved quality, and higher selling prices. Nevertheless, most artisans remain within the low-income category, with over 54% earning less than IDR 1,450,000 per month. Challenges such as limited market access, a lack of young artisan regeneration, and insufficient training persist. Therefore, this study recommends strengthening the policy with an integrated approach that includes entrepreneurship training, digital marketing, and the development of accessible sales and distribution facilities. It is hoped that this research will contribute to policymaking aimed at enhancing the role of the creative economy in local development rooted in cultural wisdom. Keywords: Government Policy, Noken, Productivity, Income, Mama-Mama Papua, Economic Empowerment, Local Wisdom